Ocular Biometric Changes Following Scleral Buckle Surgery for Rhegmatogenous Retinal Detachment - SHILPA Y D; SOWMYA SHREE B V; HEMALATHA B C; KALPANA BADAMI NAGARAJA; KAVITHA L TUMBADI (Nepalese Journal of Ophthalmology, 2026)
Introduction: Rhegmatogenous retinal detachment (RRD) is separation of neurosensory retina and Retinal Pigment Epithelium, due to full-thickness retinal breaks. Scleral Buckling (SB) is extraocular procedure done to reattach retina by counteracting vitreoretinal traction and altering globe’s geometry. Objective: To study various ocular changes and visual outcomes after buckling among patients of RRD. Methodology: A longitudinal observational study was conducted with prospective data collection in a tertiary health care centre from 2019 November to 2021 December after ethical clearance. It included 40 RRD patients who underwent scleral buckling (sizes 279, 276, and 281), recruited by consecutive sampling technique. Study excluded tractional detachment or pathologies affecting retinal visualisation. All patients were evaluated for visual acuity, refraction, intraocular pressure (IOP), axial length (AL) and anterior chamber depth (ACD) both preoperatively and post-operatively at one week, one month, and three months. Statistical analysis was done with Microsoft Excel Sheet using appropriate statistical tests. Result: Visual acuity showed significant (p-value <0.05) improvement at three months post-operatively. Mean AL increased from pre-operative 24.15 mm to 26.00 mm at one week, decreased to 25.55 mm at one month and further reduced to 25.02 mm at three months post-operatively. Mean ACD decreased from pre-operative 3.20 mm to 2.60 mm at one week, then 2.81 mm at one month and three months post-operatively. Mean IOP rose from pre-operative 12.10 mmHg to 16.45 mmHg at one week, 14.10 mmHg at one month and 13.95 mmHg at three months postoperatively. At three months, Compound myopic astigmatism was noted in 75% of patients on AR and 45% on manual refraction. Conclusion: The ocular biometric changes following buckling tend to gradually return to baseline, along with visual improvement. These findings support the safety and efficacy of the procedure; also emphasising the importance of continued post-operative monitoring to ensure optimal visual outcomes.